2019
DOI: 10.22581/muet1982.1901.03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artificial Aging Temperature on Mechanical Properties of 6061 Aluminum Alloy

Abstract: Aluminum alloys have been attracted by several engineering sectors due to their excellent strengthweight ratio and corrosion resistant properties. These are categorized into 1, 2, 3, 4, 5, 6, 7and 8xxx on the basis of alloying elements. Among these 6xxx series contains aluminum–magnesium–silicon as alloying elements and are widely used in extruded products and automotive body panels. The major advantages of these alloys are good corrosion resistance, medium strength, low cost, age hardening response no yield p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…According to [17], preheat application can increase the strength and toughness of welding results and reduce the risk of crack. In Figure 13, the chart shows that by increasing the aging temperature, the tensile strength will also increase, the same results were obtained in research conducted by [18]. It can be concluded that preheat treatment and aging PWHT affected the tensile strength of the material.…”
Section: Tensile Test Resultssupporting
confidence: 68%
“…According to [17], preheat application can increase the strength and toughness of welding results and reduce the risk of crack. In Figure 13, the chart shows that by increasing the aging temperature, the tensile strength will also increase, the same results were obtained in research conducted by [18]. It can be concluded that preheat treatment and aging PWHT affected the tensile strength of the material.…”
Section: Tensile Test Resultssupporting
confidence: 68%
“…Such modification is beneficial to restrain crack propagation, leading to improved ductility [14]. The positive effect of increasing Si content from 1.5% to 6% in a 7075-T6 alloy on strength has also been reported [15].…”
Section: Main Elementsmentioning
confidence: 84%
“…Si provides the fluidity of the alloy and improves the casting ability. Mg is added to improve its heat treatment properties and increase its strength (Kumar et al, 2015;Şimşek and Özyürek, 2019).…”
Section: Introductionmentioning
confidence: 99%